A nomogram for perioperative prognostic risk‐assessment in twin–twin transfusion syndrome. (21st November 2012) - Stirnemann, J. J.; Nasr, B.; Essaoui, M.; Bussieres, L.; Ville, Y.
ABSTRACT Objective Prognostic assessment in twin‐to‐twin transfusion syndrome (TTTS) is ill‐defined. The objective of this study is to define a perioperative prognostic score for TTTS treated by percutaneous laser coagulation. Methods Consecutive cases of TTTS treated by percutaneous fetoscopic laser coagulation over a 6‐year period were reviewed. Twin survival at 28 days was considered using a 3‐level polytomous variable defined by 0, 1, or 2 fatal events. A multivariate prognostic analysis with internal validation was conducted using gestational age at diagnosis, weight discordance, umbilical artery, and ductus venosus abnormalities in the donor and the recipient respectively, cervical length, selectivity of surgery, and transplacental approach. Results On the basis of 507 cases, the perinatal survival rate of 2 and 1 twin was 46.2% and 31.5%, respectively. Statistically significant factors included umbilical artery abnormalities in the donor, gestational age, and transplacental approach, but with different effects regarding survival of 0, 1, or 2 twins. A scoring chart was subsequently constructed together with a nomogram for both a preoperative and immediate post‐operative prognostic assessment. Conclusion Part of the prognosis can be anticipated by perioperative findings. Although further validation is required, the presented nomogram should help unify the prognostic assessment in TTTS. © 2012 John Wiley & Sons, Ltd.